EFFECT OF MYCORRHIZAL INOCULATION AND SUBSTRATE COMPOSITION ON SEEDLING GROWTH OF TWO ATLANTIC FOREST TREE SPECIES - Oliveira Júnior, Joel Quintino; Silva, Ana Caroline Rodrigues da; Silveira, Paulo Victor Moreira da; Jesus, Ederson Conceição; Pereira, Marcos Gervasio Gervasio (Floresta, 2019)
The search for more efficient biotechnological tools for forest regeneration has increased over the past decades. Mycorrhizal inoculation is a valuable strategy to promote seedling growth, but its efficiency depends on the substrate used. This study aimed to investigate the effects of arbuscular mycorrhizal fungal inoculation and different types of substrates on the growth of Pseudobombax grandiflorum and Apuleia leiocarpa seedlings. Experiments were carried out under greenhouse conditions in a completely randomized 6 × 2 factorial design (six substrates and two inoculation levels) with six replications of 12 treatments. Both species showed similar growth patterns. Plants grown in inoculated substrates composed of 70% Cambisol and 30% bovine manure or 80% Cambisol and 20% Biomix showed improved nutritional status. These substrates had good physical and chemical characteristics (pH and P and N levels), which favored plant development and mycorrhizal symbiosis. P. grandiflorum seedlings showed enhanced growth in inoculated substrate composed of 80% Cambisol and 20% Biomix and in inoculated Cambisol fertilized with P. For A. leiocarpa, the best results were observed for seedlings grown in inoculated substratescomposed of 80% Cambisol and 20% Biomix, 70% Cambisol and 30% bovine manure, or Cambisol fertilized with P.